CONTEXTUALIZED INSTRUCTION FOR SPEECH COMMUNICATION - GIDO, NATHANIEL G.; Lotes M. Rojoca; Lyndel J. Cabañero3; Maricar Cañedo; Ivie De La Cruz; Sulpicia Villaceran6 (International Journal of Multidisciplinary Research and Studies, 2022)
In the twenty-first century, educators must tackle the issue of the modern period. The results of the study will assist school administrators in providing guidance to all English teachers regarding the adoption of contextualized instruction in teaching the students in order to achieve lifelong learning that can be applied in their real life. With a mean of 1.032, the fluency and accuracy of the 31 pupils fall into the category of needing improvement. The mental structure of the kids could not be sequential, which could skew the coherence of thinking units. Numerous observations, according to Labastida (5), demonstrated that kids struggle with thinking, expressing themselves, and communicating. These can be seen in class discussions when students are reluctant to participate in them. While 13 of the responders had good content in their responses. However, 18 of the pupils had content that needed to be improved. Table 2 displays the respondents’ entry-level scores. Thirty-one (31) pupils fall under the "needs improvement" category. This has implications for organizing in that it allows students to write on a particular area of interest, but there are drawbacks to the way thoughts are put together. According to Howard (88), writing that is well-organized is crucial not just for learning but also because it serves knowledge first and communication second. Table 3 shows the respondents’ post-test speaking score following their exposure to contextualized instruction. There were 10 students whose accuracy and fluency fit the good group, and 20 students whose accuracy and fluency fit the requires improvement category. With a mean score of 1.290, it is possible that kids’ speech is slurred and their thoughts are disjointed. Wilkins, who was cited by Flores (11), and who asserted that nothing can be communicated without grammar and vocabulary, can be used to corroborate this. There were 14 respondents whose organization fell into the "good" category; however, 16 respondents, with a mean score of 1.419, fell into the "needs improvement" category. This indicates that students have a sense of organization in their writing, even though some organizational tools are only sporadically used. According to the data, the respondents’ speaking score at entrance level, specifically in terms of fluency and accuracy, was 0.032, whereas their post-test score was 1.290.